ANALISIS PENGARUH SURPLUS ARUS KAS BEBAS, AUDIT EKSTERNAL DAN KOMITE AUDIT TERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan Jasa non Keuangan yang Terdaftar di Bursa Efek Indonesia) - Intan Permata Sari; Agus Purwanto (Diponegoro Journal of Accounting, 2018)
This study aims to examine the effect of surplus free cash flow, audit quality, audit tenure, audit committee size and audit committee meeting frequency on earnings management. Dependent variable used in this study is earnings management. Independent variables used in this study are audit tenure, audit committee size and audit committee meeting frequency. Control variables used in this study are absolute total asset, firm size, leverage, dan relative cash flow.This study uses secondary data from annual reports and financial statements on service companies listed on Indonesia Stock Exchange during 2015-2016. The sampling method used in this study is purposive sampling. Total sample in this study are 101 samples. This study uses multiple regression analysis method to examine the effect of surplus free cash flow, audit quality, audit tenure, audit committee size and audit committee meeting frequency on earnings management. The result of this study indicate that audit quality had negative effect on earnings management. However, surplus free cash flow, audit tenure, audit committee size and audit committee meeting frequency had not a significant effect on earnings management.